The Effect of Learning Method and Verbal Intelligence on English Writing Skill of VIII Grade Students - Jhoni Lagun Siang; Jafar Dahlan; Muhammad Agus Umar (International Journal of Education, Information Technology, and Others, 2020)
The purpose of this study is to obtain empirical data about the Effect of Learning Method and Verbal Intelligence on English Writing Ability Grade VIII students of SMP Negeri 11 Tidore Kepulauan. This research uses experimental method with 2x2 treatment design, the method of taking is done by using research principles that is the treatment of sexual (treatmen). Treatment is given on the subject of research to improve students' English appeal. The independent variables consist of active variable (treatment) and attribute variable (moderator). The variable used is drill learning method and learning method that is moderator variable consist of high verbal intelligence and low verbal intelligence. This research was conducted at SMP Negeri 11 Tidore Kepulauan. The result of the research shows that: (1) the ability to write English students who follow the method of learning drill is higher than the students who according to the method of learning lecture (2) there is the interaction effect between the students The learning method and the verbal intelligence on students' ) Ability to write English students The method of learning drill with high verbal intelligence higher than student learning outcomes Methods lecture lectures with high verbal intelligence (4) Ability to write English students The method of learning drill with verbal gender is lower than the ability to write English students in which the method of lectures with low verbal intelligence.